Strategi dan Pergeseran Makna Penerjemahan Istilah Religi dalam Komik Kamisama Hajimemashita Volume 1-7 Karya Suzuki Julietta - Dewi, Rosmala; Oeinada, I Gede; Budiana, I Made (Humanis, 2016)
Religious aspect is very important to human life. In translating religious terms, the translator must know the meaning of the text to prevent meaning shift. The title of this study is Translation Strategy and Meaning Shift of Religious Terms in Kamisama Hajimemashita Comic Volume 1-7 by Suzuki Julietta. The theories used for analyzing are classification of basic religious elements by Durkheim in Koentjaraningrat (2005), translation strategies by Baker (1992) and componential analysis by Bell (1993). There are six translation strategies that are used to translate religious terms. The selection of translation strategies can caused meaning shift.